Learning for Success: Distance Education Students’ use of their Learning Materials - Smith, A.; Smith, E. (Journal of University Teaching and Learning Practice, 2006)
This paper reports the results of a research project investigating the usethat Distance Education (DE) students at university make of the learningmaterials that are supplied to them. The research is based on a survey of998 DE students enrolled in ten undergraduate subjects spread across allfive Faculties at Charles Sturt University (CSU) in New South Wales,Australia. CSU is Australia’s largest DE provider of higher education. Theproject addressed the following questions:• The extent to which DE undergraduate students use their learning materials.• The extent to which students undertake the learning activities that are oftenincorporated in learning materials.• The extent to which students obtain learning materials beyond the printedlearning materials, especially their use of library facilities and the internet toresearch topics in their study programs.• The way in which DE undergraduate students approach their study and thestudy strategies that they adopt.The paper reports the major conclusions from the survey. It was found thatthe majority of students read most or all of the learning materials that weresent to them. They relied heavily upon the prescribed textbooks, did someadditional reading as recommended, to a limited extent carried outadditional reading beyond that recommended, and worked through theprovided learning materials in a methodical manner. They generallycompleted, in their minds if not always on paper, the study tasks embeddedin the learning materials. Those students that read less and paid lessattention to study tasks tended to study in a way that was focused onpassing assessment tasks. Overall the study provides a strong argumentfor the retention of printed learning materials as students seem to work wellwith them, and the more effectively students use them the better they seemto perform.